An Analysis of Physician Productivity and Self-Sustaining Revenue Generation in a Free-Standing Emergency Department Medical Scribe Model. (29th December 2015) - Dawkins, Brody; Bhagudas, Komal N.; Hurwitz, Joshua; Tyndall, J. Adrian; Guerra, Marcelo E.; Falgiani, Michael; Payton, Thomas F.; Allen, Brandon R.
Abstract : Objectives . A free-standing emergency department (FSED) is a facility that provides comprehensive emergency medical care similar to a traditional emergency department but is not attached to a hospital campus. Medical scribes are increasingly likely to work in free-standing emergency departments. The purpose of this study was to retrospectively investigate the benefits of a scribe program in an FSED. Methods . A retrospective, Institutional Review Board-approved analysis from December 1, 2013, to February 1, 2015, of free-standing emergency department medical data was extracted to determine if scribed charts resulted in increased revenue and improved throughput. Results . When scribes are present in the FSED there is a small, but statistically significant, decrease in time from patient arrival to provider by 2.74 minutes. Scribed charts collected 4.69 more per chart and resulted in an increase in productivity. Incremental cost effectiveness ratios resulted in proven cost-utility with a net-positive effect. Conclusion . While there are some gains in terms of operational metrics and provider productivity with the addition of scribes to a free-standing emergency department, there is a net-positive financial impact of scribes. Implementing a scribe program at a FSED is cost-effective and justified from both an operational and a financial analysis.